Neurociencia y derecho: problemas y posibilidades para el quehacer jurídico - Cárdenas Krenz, Arturo Ronald (2016)
This article is about the connection between neuroscience and the effects on legal rules. There are several brain studies that question the existence of free will. Free will is the basis of legal docrine. This article attempts to determine whether or not free will exists, and to review the possibilities offered by neuroscience, with new means to seek the truth, marketing development, determination of capacity and other issues, by reviewing the benefits and risks. Finally, it addresses the need to ensure the respect of human rights with these new neuroscientific technologies.